5G and up to 6G - V. Basil Hans (International Journal of Wireless Security and Networks, 2025)
The 5th generation of mobile networks is called 5G, and the next generation, 6G is expected to arrive soon. With the promise of faster speeds, less latency, and increased connectivity, 5G technology has revolutionized mobile communications. However, the 6G vision is already taking shape as the need for high-performance networks keeps increasing. By offering ultra-high-speed communication, smooth artificial intelligence (AI) integration, extensive Internet of Things (IoT) connectivity, and support for holographic communications and immersive technologies like augmented and virtual reality (AR/VR), this next-generation network is anticipated to surpass the capabilities of 5G. Terahertz (THz) frequency bands are expected to be used by 6G, allowing for previously unheard-of data throughput and decreased latency. These features are essential for applications like remote healthcare, smart cities, autonomous systems, and next-generation industrial automation. The developments in 5G technology, the expected transition to 6G, and the obstacles to its implementation, such as spectrum management, network security, energy efficiency, and international interoperability, are all covered in this study. There have been notable turning points in the development of mobile communication technologies, with each generation bringing notable advancements in functionality, speed, and capacity. Unprecedented connection has already been made possible by the 4G to 5G shift, enabling a new generation of innovations including smart cities, driverless cars, and improved augmented reality experiences. But as we move forward, it is becoming clearer that even quicker, more effective, and scalable networks are required. The next wave of wireless communication technology, 6G, is here. In order to meet the constantly increasing need for more data, faster speeds, and pervasive connection, 6G is anticipated to expand on the capabilities of 5G. 6G proposes a fully integrated and intelligent network environment that smoothly supports a wide range of future technologies, including as edge computing, artificial intelligence, and the Internet of Things (IoT), in contrast to 5G, which is solely focused on improving mobile broadband. 6G seeks to provide near-instantaneous data transfer and near-zero latency by utilizing higher frequency bands, such as the terahertz (THz) spectrum, opening up applications that were previously thought to be far off. This study looks at the expected characteristics and developments of 6G, the obstacles that need to be removed to make it a reality, and its possible uses in a world that is getting more digital and linked by the day. Understanding 6G's potential to transform industries, enhance lives, and open up completely new avenues for global connectivity is crucial as we set out on this path.
Keywords: 5G & 6G network; Internet of things (IoT); communication; faster speeds; technologies; worldwide connectedness